Global variations in the level of cancer-related research activity and correlation to cancer-specific mortality: Proposal for a global curriculum. Issue 1 (January 2018) - Are, C.; Caniglia, A.; Malik, Mohammed; Smith, L.; Cummings, Charmaine; Lecoq, Carine; Berman, R.; Audisio, R.; Wyld, L.
Abstract: Introduction: The aim of this study was to analyze global variations in the level of cancer-related research activity and correlate this with cancer-specific mortality. Methods: The SCOPUS database was explored to obtain data relating to the number of cancer-related publications per country. Cancer-specific mortality rates were obtained from the World Health Organization. Global variations in the level of scholarly activity were analyzed and correlated with variations in cancer-specific mortality. Results: Data for 142 countries were obtained and significant variations in the level of research activity was noted. The level of research activity increased with rising socio-economic status. The United States was the most prolific country with 222, 300 publications followed by Japan and Germany. Several countries in different regions of the world had a low level of research activity. An inverse relationship between the level of research activity and cancer-specific mortality was noted. This relationship persisted even in countries with a low level of research activity. The socioeconomic status of a nation and geographic location (continent) had a mixed influence with an overall apparent correlation with cancer-related research activity. Conclusion: This study demonstrates significant global variation in the level of cancer-related research activity and a correlation with cancer-specific mortality. The presence of a minimum set of standards for research literacy, as proposed by the European Society of Surgical Oncology and the Society of Surgical Oncology may contribute to enhanced research activity and improve outcomes for cancer patients worldwide. Abstract : Synopsis: The results of this study demonstrated significant global variations in cancer-related research activity and a correlation to cancer-specific mortality. These results call for a global curriculum in research literacy which has been developed by the Society of Surgical Oncology and the European Society of Surgical Oncology.